Factors affecting the dominance hierarchy dynamics in a hummingbird assemblage. Issue 3 (14th July 2018) - Márquez-Luna, Ubaldo; Lara, Carlos; Corcuera, Pablo; Valverde, Pedro Luis
Abstract: Intra and interspecific competition for nectar play an important role in hummingbird communities. Larger sized species usually exclude smaller species from the rich floral resources. However, it has been recently postulated that the competitive advantages of a large body size decline as the evolutionary distance between the contending species increases. In this study, we analyzed dominance hierarchy dynamics in a hummingbird assemblage in central Mexico. By monitoring hummingbird territories established in three plant species through 1 year, we assessed the effects of energy within territories and the territory owners identity in the frequency of inter and intraspecific encounters. We also evaluated if these factors affect the dominance of larger species when they compete against smaller distantly related contenders. Our results show that their frequency of intraspecific encounters was related with the identity of the territory's owner. On the contrary, the frequency of interspecific encounters was related with both the territory and the identity of the territory's owner. We did not find a significant difference between the number of encounters dominated by larger and smaller species and their contenders. However, the increase in genetic distance between contenders was positively associated with a higher frequency of encounters dominated by small hummingbirds. Our results showed that the ecological factors and evolutionary relationships among contenders play important roles in the dominance hierarchy dynamics.